PENERAPAN METODE PROYEK DALAM PROSES PEMBUATAN ALAT PENJERNIHAN AIR MENGGUNAKAN PRINSIP KOLOID PADA SISWA SMA - Yanti, Yuli; Harun, A. Ifriany; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThe purpose of the research is to find out and to describe the students? skills of SMA Negeri 1 Sungai Ambawang in planning, arranging schedule and presenting the  water purifier products, as well as to find out whether the water which is produced has met the criteria of odorless, colorless, tasteless and unclouded. This research use pre-experiment method with one shot case study design. The technique of data collecting which being used is direct observation technique by using group skill sheet and direct communication through interview. The population of this research is class XI IPA 1 and XI IPA 2 SMA Negeri 1 Sungai Ambawang. Since the sample is homogenous, the research sampling is determined by using random sampling and it is obtained that class XI IPA 1 which consist of 30 students has been chosen as the sample of the research. The result of the analysis shows that the students? skill on making plan and arranging schedule is on very good category, meanwhile the students? skill on presenting the product is on enough category. The analysis also finds out that 33,33 % of the water which was produced by the water purification has been fulfilled the quality of clean water..Keyword:Project Method, Water purification, colloid